Thymic Function and T-Cell Receptor Repertoire Diversity: Implications for Patient Response to Checkpoint Blockade Immunotherapy - Cardinale, Antonella; De Luca, Carmen Dolores; Locatelli, Franco; Velardi, Enrico (Frontiers in Immunology, 2021)
The capacity of T cells to recognize and mount an immune response against tumor antigens depends on the large diversity of the T-cell receptor (TCR) repertoire generated in the thymus during the process of T-cell development. However, this process is dramatically sensitive to immunological insults, such as that caused by cytoreductive cancer therapies, infections, and the physiological decline of thymic function with age. Impaired thymic function and a skewed TCR repertoire can have significant clinical consequences. The presence of an adequate pool of T cells capable of recognizing specific tumor antigens is a prerequisite for the success of cancer immunotherapy using checkpoint blockade therapy. However, while this approach has improved the chances of survival of patients with different types of cancer, a large proportion of them do not respond. The limited response rate to checkpoint blockade therapy may be linked to a suboptimal TCR repertoire in cancer patients prior to therapy. Here, we focus on the role of the thymus in shaping the T-cell pool in health and disease, discuss how the TCR repertoire influences patients’ response to checkpoint blockade therapy and highlight approaches able to manipulate thymic function to enhance anti-tumor immunity.